Pharmacokinetics and tissue distribution analysis of ginsenoside Rh3 in rats using a novel LC-MS/MS quantification strategy - Hu, Cong; Wang, Yuheng; Liu, Yu; Wang, Xiaojing; Song, Peifang; Ma, Hong; Yang, Ling (Frontiers in Pharmacology, 2025)
Introduction:Ginsenoside Rh3 (GRh3), a rare ginsenoside, demonstrates diverse pharmacological activities in vitro; however, the lack of pharmacokinetic and tissue distribution data has limited its translation to in vivo applications. This study aimed to develop and validate a novel liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for quantifying GRh3 in rat biological matrices and to characterize its pharmacokinetic profile and tissue distribution following oral administration.Methods:A validated LC-MS/MS method was established for the quantification of GRh3 in rat plasma and tissues. Male Sprague-Dawley rats received an oral dose of GRh3 (100 mg/kg), and plasma samples were collected up to 72 h post-dose for pharmacokinetic analysis. Tissue samples (intestine, stomach, liver, brain, etc.) were collected at the time corresponding to the maximum plasma concentration for distribution analysis.Results:The LC-MS/MS method showed excellent precision, accuracy, and extraction recovery (≥ 85%), with minimal matrix effects. GRh3 exhibited a prolonged elimination half-life (14.7 ± 1.7 h), a low clearance rate (13.0 ± 3.8 L/h/kg), and a high volume of distribution (280.4 ± 109.3 L/kg). Tissue distribution analysis revealed the highest GRh3 concentrations in the intestine (15445.2 ng/g), followed by the stomach (2906.7 ng/g) and liver (1930.8 ng/g). Notably, GRh3 was able to cross the blood-brain barrier, with significant accumulation observed in the hippocampus (520.0 ng/g).Discussion:The prolonged elimination and extensive tissue distribution of GRh3, particularly its ability to penetrate the brain, indicate potential therapeutic benefits or neurotoxic risks involving the central nervous system. The mechanism underlying its blood-brain barrier permeability warrants further investigation, potentially involving transporter-mediated uptake or modulation of barrier integrity. These findings provide a foundation for optimizing GRh3 dosing regimens and guiding future preclinical studies.